PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI SMP SE-NIAS BARAT - Soziduhu Gulo; Bernadetha Nadeak; Hotner Tampubolon (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2021)
The principal has an important role in improving the performance of his teachers. The results of preliminary observations found that principals are authoritarian by making decisions without involving teachers. Gives a bad impression to subordinates who later builds a culture that affects the teacher's performance. This type of research is quantitative using a survey method with a correlation approach, related to the purpose for